Preparation and Uses of Chlorinated Glycerol Derivatives - Anna Canela-Xandri; Mercè Balcells; Gemma Villorbina; Paul Christou; Ramon Canela-Garayoa (Molecules, 2020)
Crude glycerol (C3H8O3) is a major by-product of biodiesel production from vegetable oils and animal fats. The increased biodiesel production in the last two decades has forced glycerol production up and prices down. However, crude glycerol from biodiesel production is not of adequate purity for industrial uses, including food, cosmetics and pharmaceuticals. The purification process of crude glycerol to reach the quality standards required by industry is expensive and dificult. Novel uses for crude glycerol can reduce the price of biodiesel and make it an economical alternative to diesel. Moreover, novel uses may improve environmental impact, since crude glycerol disposal is expensive and dificult. Glycerol is a versatile molecule with many potential applications in fermentation processes and synthetic chemistry. It serves as a glucose substitute in microbial growth media and as a precursor in the synthesis of a number of commercial intermediates or fine chemicals. Chlorinated derivatives of glycerol are an important class of such chemicals. The main focus of this review is the conversion of glycerol to chlorinated derivatives, such as epichlorohydrin and chlorohydrins, and their further use in the synthesis of additional downstream products. Downstream products include non-cyclic compounds with allyl, nitrile, azide and other functional groups, as well as oxazolidinones and triazoles, which are cyclic compounds derived from ephichlorohydrin and chlorohydrins. The polymers and ionic liquids, which use glycerol as an initial building block, are highlighted, as well.